2011
DOI: 10.1136/bmj.d35
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus infection and type 1 diabetes mellitus: systematic review and meta-analysis of observational molecular studies

Abstract: Objective To review the association between current enterovirus infection diagnosed with molecular testing and development of autoimmunity or type 1 diabetes. Design Systematic review and meta-analysis of observational studies, analysed with random effects models. Data sources PubMed (until May 2010) and Embase (until May 2010), no language restrictions, studies in humans only; reference lists of identified articles; and contact with authors. Study eligibility criteria Cohort or case-control studies measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
382
1
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(405 citation statements)
references
References 56 publications
17
382
1
5
Order By: Relevance
“…25,26 In this context, our data are consistent with the recently published metaanalysis of 33 prevalence studies suggesting that enterovirus infection is common among patients with T1D. 27 Our microarray data provided additional evidence to support the notion that viral infection may have contributed to the onset of T1D in the two quadruplets. Notably, cellular anti-viral responses were more prominent in the diabetic sisters where the antiviral signalling of interferons was the most significantly affected pathway.…”
Section: Discussionsupporting
confidence: 90%
“…25,26 In this context, our data are consistent with the recently published metaanalysis of 33 prevalence studies suggesting that enterovirus infection is common among patients with T1D. 27 Our microarray data provided additional evidence to support the notion that viral infection may have contributed to the onset of T1D in the two quadruplets. Notably, cellular anti-viral responses were more prominent in the diabetic sisters where the antiviral signalling of interferons was the most significantly affected pathway.…”
Section: Discussionsupporting
confidence: 90%
“…Epidemiological studies have suggested that infections with enteroviruses, in particular those of the coxsackie B virus (CVB) serotypes, may be linked to islet autoimmunity and development of type 1 diabetes [1][2][3][4][5]. Other observations suggesting that infections with these viruses have a causative role in diabetes development come from studies that found enteroviruses more frequently in pancreases [6][7][8] and, in some studies, also gut biopsies [9][10][11], from patients with type 1 diabetes compared with healthy controls.…”
Section: Introductionmentioning
confidence: 89%
“…Based upon the observations linking enterovirus infections to the development of type 1 diabetes [1][2][3][4][5], it would be expected that such infections are more common in countries with a high disease incidence compared with those with an intermediate or low incidence. In contrast to this assumption, epidemiological studies conducted in different geographical regions of Europe have demonstrated that the frequency of enterovirus infections in the background population shows an inverse correlation to the incidence of type 1 diabetes [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Enteroviral components have been more frequently detected in blood of T1D patients, and a meta-analysis has reported a strong association between EV detection, especially CV-B, and T1D. 3 The presence of EV protein in the pancreas of T1D patients has been observed. 4 Prospective studies confirmed the link between EV and the development of pancreas islet autoimmunity.…”
Section: Introductionmentioning
confidence: 99%